Comparison of plant diversity-carbon storage relationships along altitudinal gradients in temperate forests and shrublands - Lu, Shuaizhi; Zhang, Dou; Wang, Le; Dong, Lei; Liu, Changcheng; Hou, Dongjie; Chen, Guoping; Qiao, Xianguo; Wang, Yuyouting; Guo, Ke (Frontiers in Plant Science, 2023)
Plant diversity strongly influences ecosystem functions, such as biomass carbon. However, the differences in plant diversity-carbon relationships along altitudinal gradients between forests and shrublands are poorly understood, impeding ability to manage terrestrial ecosystems and predict carbon sinks. Using data from 37962 trees of 115 temperate forests and 134 shrublands plots of Taihang Mountains Priority Reserve, we analyzed the effects of species diversity, structural diversity, and dominant species on carbon storage along altitudinal gradients in temperate forests and shrublands. We found that species diversity underpins shrubland carbon storage, but structural diversity is more important for forest carbon storage. Specifically, with increasing structural diversity, forest carbon storage increased but shrubland decreased. Besides, the relative abundance of dominant species had a ubiquitous negative indirect effect on carbon storage via species diversity in both forests and shrublands. Furthermore, altitudinal gradients altered the response mechanisms of carbon storage in forests and shrublands. Specifically, high altitudes prominently enhanced the positive relationship of carbon-structural diversity in forests and weakened the positive relationship of carbon-species diversity in shrublands. This study could help guide differentiated forests and shrublands management in reaction to environmental change